A Hypnotherapy in Midwifery Care: A Systematic Review of the Evidence and Potential Use in Clinical Practice: Hipnoterapi dalam Asuhan Kebidanan: Tinjauan Sistematik atas Evidensi dan Potensi Penggunaan dalam Praktik Klinis - aghniya, Rofana Aghniya; Widiyanti, Septi Widiyanti; Oktaviani, Ika (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, Universitas Muhammadiyah Muara Bungo, 2024)
Pregnancy, childbirth and postpartum are a series of events that significantly change a mother's life and are often accompanied by various physical and emotional challenges and problems. This review of this study was to analyze the trends and effectiveness of hypnotherapy interventions in pregnancy and childbirth nationally and internationally through electronic databases such as PubMed, MEDLINE, PsycINFO and Google Scholar to identify relevant studies. Article quality assessment uses Critical Appraisal Tools for Systematic review. The results of the literature review show that hypnotherapy interventions provide promising results in reducing labor pain, relieving anxiety, reducing symptoms of nausea and vomiting, increasing maternal satisfaction and improving the overall labor experience. Hypnotherapy can be used as one of the complementary interventions in the field of obstetrics and maternity care. Further research needs to focus on the establishment of standard protocols, experiments with random sampling methods on larger subjects and exploring the long-term effects and cost-effectiveness of hypnotherapy interventions in various obstetric treatments.